2018
DOI: 10.1002/cam4.1705
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of treatment with eribulin mesylate for metastatic triple‐negative breast cancer: Long‐term outcomes of patients treated in the US community oncology setting

Abstract: IntroductionReal‐world data are critical to demonstrate the consistency of evidence and external generalizability of randomized controlled trials (RCTs). This study examined characteristics and outcomes of metastatic triple‐negative breast cancer (mTNBC) patients treated with eribulin mesylate at community oncology practices in the United States.MethodsPhysicians identified mTNBC patients initiating eribulin between 1 January 2011 and 1 January 2014 and abstracted data into an electronic case report form (eCRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
4
12
1
Order By: Relevance
“…Toxicity was acceptable with no new safety issue. Median OS was 23 months in early lines and 14.7 months in later lines, the latter comparable to those of the EMBRACE and 301 trials 48. An Italian retrospective study on 44 heavily pretreated advanced BC patients showed longer PFS in ER-positive/HER2-negative tumors, and more favorable results have been observed in patients pretreated with first-line paclitaxel/bevacizumab in comparison to other first-line regimens.…”
Section: Eribulin In the Real-world Settingsupporting
confidence: 67%
“…Toxicity was acceptable with no new safety issue. Median OS was 23 months in early lines and 14.7 months in later lines, the latter comparable to those of the EMBRACE and 301 trials 48. An Italian retrospective study on 44 heavily pretreated advanced BC patients showed longer PFS in ER-positive/HER2-negative tumors, and more favorable results have been observed in patients pretreated with first-line paclitaxel/bevacizumab in comparison to other first-line regimens.…”
Section: Eribulin In the Real-world Settingsupporting
confidence: 67%
“…Overall, eribulin treatment in our cohort was safe, with manageable toxicities. To our knowledge, evidence from literature concerning eribulin use in mTNBC as second-line treatment is lacking, with the majority of data being from retrospective studies [14][15][16][17][18][19]. In the pooled analysis of the EMBRACE trial and Study 301, the PFS on eribulin from TNBC patients was 2.8 months, but most of these patients had received more than 1 previous chemotherapy line [12].…”
Section: Discussionmentioning
confidence: 99%
“…Real-world reports have generally noted safety findings consistent with those found in clinical trials for eribulin. Across several studies in community settings in the United States, neutropenia (31% to 32.2%) and peripheral neuropathy (19.4% to 31.3%) were consistently reported as common AEs [52][53][54]. In a Belgian expanded-access program, the most frequent AEs with eribulin were fatigue/asthenia (all grades: 73.8%; grade 3/4: 9.2%), alopecia (all grades: 54.6%), peripheral neuropathy (all grades: 46.1%; grade 3/4: 7.1%), and neutropenia (all grades: 42.6%; grade 3/4: 36.9%) [55].…”
Section: Real-world Data For Eribulinmentioning
confidence: 99%